2017
DOI: 10.1093/pch/pxx096
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between paediatric practitioners and ‘industry’

Abstract: Paediatric practitioners interact with industry representatives for many purposes but most often to receive information on new and existing products. While practitioners believe they are immune to the marketing influences exerted by these representatives, research has demonstrated otherwise. The literature suggests that the public is aware of such influences and that most people feel industry influence on practitioners is inappropriate. National guidelines go some way toward regulating practitioner-industry in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…According to the Canadian Paediatric Society (CPS), health research is a moral duty because it is the foundation for evidence-based care by all health care practitioners. 22 Zimmerman et al identified PICUs to be uniquely suited to the needs of clinical research, thanks to the availability of resources necessary to foster an environment of evidencebased, iterative work to improve the quality of care. 23 However, academic work in the field still needs to be improved.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Canadian Paediatric Society (CPS), health research is a moral duty because it is the foundation for evidence-based care by all health care practitioners. 22 Zimmerman et al identified PICUs to be uniquely suited to the needs of clinical research, thanks to the availability of resources necessary to foster an environment of evidencebased, iterative work to improve the quality of care. 23 However, academic work in the field still needs to be improved.…”
Section: Discussionmentioning
confidence: 99%
“…25 It could be argued that BMS funding encourages paediatricians and their organisations to overvalue the benefits of formula milk and be reluctant to acknowledge any adverse effects, as suggested by their own writing on the subject. 17,26 Individual paediatricians lobby professional associations to divest themselves of BMS sponsorship and in some countries, such as India and South Africa, progress is being made, 27,28 but in others the funding flow continues. 29 In the UK, a nonbinding motion was passed at the RCPCH's annual general meeting in 2016 proposing a complete break from receiving income from BMS companies, 30 but it was overturned in 2017 after a consultation of the membership which suggested that funding from "ethical" companies would be acceptable.…”
Section: Sponsorship Of Paediatric Associations By Manufacturers Of Bmentioning
confidence: 99%